INHERITANCE RIGHTS OF OUTSIDE MARRIAGE DESCENDANTS AFTER THE RULING OF THE CONSTITUTIONAL COURT NUMBER 46 OF 2010 - Abrori, Ahmad; Wibawa, Iskandar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
The aim of this research is to find out. Based on the background description above, a problem can be drawn, namely: How is the organizational performance of the Class II B Kudus State Detention Center implemented in improving public services and what are the obstacles that occur in implementing the organizational performance of the Class II B Kudus State Detention Center in improving public services? This research uses a sociological juridical approach. Sociological juridical approach, namely a research approach that examines the legal perceptions and behavior of people (humans and legal entities) and society as well as the effectiveness of the enactment of positive law in society. Implementation of the performance of the Class II B Kudus Prison in improving public services is reflected in the decision to accept prisoners, even though its main function is accepting prisoners. This is due to the unique situation in Kudus Regency which does not yet have a prison, forcing the Class IIB Kudus Detention Center to adapt and meet public needs in the criminal justice system. As a result, the detention center not only handles detainees but also inmates, having a broader impact on the criminal justice system and Kudus Regency society in general. This statement also highlights the relationship between legal structure, legal substance and legal culture in the context of public services